Mike Deodato Jr e a invasão brasileira na terra dos super-heróis (1989-2019) - Flexa, Rodrigo Nathaniel Arco e (2019)
Study of the increasing entry of Brazilian artists into the US comic books industry since late 1980. This is an editorial phenomenon that is still growing. Today, many artists from Brazil are among the most prestigious in the US market. The thesis will work with historical and theoretical studies for the analysis of the most relevant comics of the production under investigation. In this sense, the narrative will cover three moments: past, present and future (genealogy, environments and impacts). To this end, the thesis chose as protagonist of the editorial history under study the career of the Brazilian artist, the paraibano Mike Deodato Jr, one of Brazil's comics pioneers into the US industry and in full activity to the present day. Then, investigate how Brazilian artists produce according to industry standards and when - in different ways, and case by case -, their trajectories develop a visual identity that generates impacts on the United States and Brazil markets and society